The diagnosis and management of small and indeterminate lymph nodes in papillary thyroid cancer: preoperatively and intraoperatively - Hu, Ang; Tian, Jiahe; Deng, Xinpei; Wang, Zhongyu; Li, Yin; Wang, Jianwei; Liu, Longzhong; Li, Qiuli (Frontiers in Endocrinology, 2024)
Although thyroid cancer is an indolent tumor with a favorable prognosis, lymph node metastasis (LNM) serves as a major concern for many patients. Because LNM is strongly correlated with recurrence, distant metastasis, and shortened survival, a precise and timely diagnosis and following appropriate management for LNM are necessary. Clinically, the preoperative evaluation of lymph nodes has improved as a result of imaging technological advancements in this field.However, significant challenges still exist in the diagnosis of small LNs (＜1 cm in diameter), and their low volume makes it difficult to determine whether they are metastatic or benign. Therefore, the diagnostic technique for these small and indeterminate LNs (siLNs) has been one of the leading research subjects in recent years. The implementation of innovative technologies, such as contrastenhanced ultrasonography, frozen section, and molecular detection, has brought great progress to the diagnosis of siLNs. Meanwhile, the strategies for managing siLNs in clinical practice hasve evolved considerably over the past several years, with several appropriate options recommended by guidelines. In this review, we aim to provide a systematic overview of the latest studies and potential evidence about effective approaches for detecting and evaluating siLNs. Furthermore, the following management modalities of siLNs in different situations are well discussed.